2011
DOI: 10.1089/scd.2010.0333
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor-Null Allele Mice Have Hematopoietic Stem/Progenitor Cells with Abnormal Characteristics and Functions

Abstract: The aryl hydrocarbon receptor (AhR) belongs to the basic helix-loop-helix family of DNA-binding proteins that play a role in the toxicity and carcinogenicity of certain chemicals. The most potent ligand of the AhR known is 2,3,7,8-tetracholorodibenzo-p-dioxin. We previously reported tetrachlorodibenzo-p-dioxin-induced alterations in numbers and function of hematopoietic stem cells (HSCs). To better understand a possible role of the AhR in hematopoiesis, studies were undertaken in young adult AhR null-allele (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
82
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 65 publications
(79 reference statements)
21
82
0
Order By: Relevance
“…These analyses suggested that the AhR plays an important role in blood cell development and were consistent with previous studies. 22,23,26,44 In our studies, we have found that the use of a nontoxic AhR agonist in a directed differentiation scheme dramatically increases the number of HPs and resultant cells. This finding is important in that, traditionally, the evolutionarily conserved AhR has been studied for its role in environmental chemical-induced toxicity, and in our system it is shown to be involved in the growth and the differentiation of at least 2 crucial blood cell types.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…These analyses suggested that the AhR plays an important role in blood cell development and were consistent with previous studies. 22,23,26,44 In our studies, we have found that the use of a nontoxic AhR agonist in a directed differentiation scheme dramatically increases the number of HPs and resultant cells. This finding is important in that, traditionally, the evolutionarily conserved AhR has been studied for its role in environmental chemical-induced toxicity, and in our system it is shown to be involved in the growth and the differentiation of at least 2 crucial blood cell types.…”
Section: Discussionmentioning
confidence: 64%
“…[5][6][7][8][9][10]21 Importantly, recent breakthrough studies suggest that the AhR plays a critical role in nominal hematopoietic stem cell (HSC) growth and differentiation. 22,23 For example, AhR 2/2 mice are characterized by an increased number of bone marrow HSCs 22 and a commensurate increased propensity to develop lymphomas. 24 These insights led to the hypothesis that the AhR, activated by endogenous ligands, regulates stem cell growth and/or differentiation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 In addition to platelets, altered red and leukocyte cell counts have also been observed in AhR KO mice. 27 Therefore, AhR likely impacts many hematopoietic stages and lineages and answers on its specific role in megakaryopoiesis might require a tissue-restricted KO approach.…”
Section: Cd41mentioning
confidence: 99%